GROWTH AND SURVIVAL OF SEEDLINGS AND SAPLINGS IN THE LOGGED - OVER FOREST, KINTAP, SOUTH KALIMANTAN - Yusuf S. Jafarsidik (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2004)
A study on demography, growth and survival of seedlings and saplings was conducted in the Hutan Kintap concenssion, South Kalimantan, Indonesia. The aim of the study was to monitor pattern of growth of seedlings and saplings among different types of logged - over forest, including the newly logged - forest, older logged - over forests (treated and untreated), and un-logged-forest patches. The study began in 1991, and nineteen of 0.25 ha plots were set up in a total of six blocks designated as consecutively A, B, C, D, E and F. Block A was a newly logged forest and had five plots, and Block B - D were in forest which had been logged in 1979. Block B (five plots) had received no silvicultural treatment, while Block C (five plots) and D (one plot) had been lightly thinned after felling and further Block C received a further thinning treatment Block E (one plot) had been heavily thinned, and Block F (2 plots) was an un-logged control. The density of seedling varied within the study sites, and averaged from 47,000 ha